(untitled) (Journal of Science and Technology, 2016)
A high - resolution proton nuclear magnetic resonance (Nmr) was used to investigate platelet membrane lipid composition of subjects who have been definitively diagnosed as having various forms of coronary heart disease (CAD). The one dimensional (1D) proton spectra were recorded at a temperature of 298° K in Fourier transform(FT) mode with 16K data points, using a 45° detection pulse and 2.0 acquisition time with a solvent presaturation during relaxation to remove excess water signal. The major phospholipids and cholesterol present were identified and estimated and compared to those of normal individual’s platelet membrane. Platelet cholesterol content as analysed by the proton Nmr in all the 3 patients investigated were significantly elevated (p<0.00001). In contrast, arachidonic acid level in the three patients were significantly reduced (P<0.0002) as well as phosphatidylcholine (p<0.048) and phosphatidylethanolamine (p<0.016). the degree of unsaturation in the various structural phospholipids were also compared and was found to be less than those of the controlsubject. Cholesterol: phospholipid ratio were also raised in the patients (p<0.0016). this work has shown that vital clinical information could be derived for lipid analysis by proton nuclear resonance could be of clinical significance I the management of such patients.